GAMBARAN UMUM PASIEN RAWAT JALAN DI RUMAH DAN EVALUASI PELAYANAN INFORMASI OBAT DI INSTALASI FARMASI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Syafitri, Anggun; Marbun, Viktor Edyward (Jurnal Penelitian Farmasi & Herbal, 2023)
Drug Information Service (PIO) is one of the standards that must be applied to improve the best pharmaceutical services. Drug information services are very necessary for patients because complete drug information can determine the success of self-therapy at home, especially for outpatients. Provision of drug information has an important role to achieve optimal treatment results, Provision of drug information has an important role to achieve optimal treatment results, so as to improve the quality of life of patients. Pharmaceutical services at this time have shifted their orientation from drugs to patients referring to pharmaceutical care. This study used a descriptive observational research method with a cross sectional design and used a quantitative approach. This research was conducted at the Outpatient Installation of Sembiring Deli Tua General Hospital. The population is the entire object used in the study.